Urogenital pathogens, associated with Trichomonas vaginalis, among pregnant women in Kilifi, Kenya: a nested case-control study - Masha, S; Cools, P; Descheemaeker, P; Reynders, M; Sanders, E; Vaneechoutte, M (BioMed Central, 2018)
Background Screening of curable sexually transmitted infections is frequently oriented towards the diagnosis of chlamydia, gonorrhea, syphilis and trichomoniasis, whereas other pathogens, sometimes associated with similar urogenital syndromes, remain undiagnosed and/or untreated. Some of these pathogens are associated with adverse pregnancy outcomes. Methods In a nested case-control study, vaginal swabs from 79 pregnant women, i.e., 28 T. vaginalis-positive (cases) and 51 T. vaginalis-negative (controls), were screened by quantitative PCR for Adenovirus 1 and 2, Cytomegalovirus, Herpes Simplex Virus 1 and 2, Chlamydia trachomatis, Escherichia coli, Haemophilus ducreyi, Mycoplasma genitalium, M. hominis, candidatus M. girerdii, Neisseria gonorrhoeae, Streptococcus agalactiae, Treponema pallidum, Ureaplasma parvum, U. urealyticum, and Candida albicans. Additionally, we determined whether women with pathogens highly associated with T. vaginalis had distinct clinical signs and symptoms compared to women with T. vaginalis mono-infection. Results M. hominis was independently associated with T. vaginalis (adjusted odds ratio = 6.8, 95% CI: 2.3–19.8). Moreover, M. genitalium and Ca M. girerdii were exclusively detected in women with T. vaginalis (P = 0.002 and P = 0.001), respectively. Four of the six women co-infected with T. vaginalis and Ca M. girerdii complained of vaginal itching, compared to only 4 out of the 22 women infected with T. vaginalis without Ca M. girerdii (P = 0.020). Conclusion We confirm M. hominis as a correlate of T. vaginalis in our population, and the exclusive association of both M. genitalium and Ca. M. girerdii with T. vaginalis. Screening and treatment of these pathogens should be considered.